Psychological Well-being and Demographic Factors among Private Company Employees in a Highly Urbanized City, Western Visayas, Philippines - Moleño, Mary Edillis O.; Doromal, Araceli C. (Philippine Social Science Journal, 2024)
Employee well-being is crucial for organizational success, influenced by factors like workplace design, leadership, and organizational culture, with the latter significantly impacting mental health. Psychological well-being is multifaceted, shaped by individual demographics (age, sex), job resources and stressors, and organizational factors. In the Philippines, well-being is recognized as crucial, with the government issuing guidelines for mental health in the workplace. This study examines the psychological well-being of 101 employees in three private companies in Central Visayas, Philippines, revealing moderate levels across all dimensions, which indicates a generally positive work environment with room for improvement. Contrary to expectations, demographic factors like age and tenure are not significantly correlated with well-being. However, a significant relationship between sex and psychological well-being highlights potential gender-based disparities. These findings underscore the need for personalized well-being initiatives and further research with larger, more diverse samples to explore the complex factors contributing to employee well-being in the Philippines, particularly gender differences, and to develop tailored interventions.